Brzeskie potomstwo Biblii Radziwiłłowskiej. Sprawy i słowa Jezusa Krystusa oraz Wtore księgi Łukasza świętego Tomasza Falconiusa - Siwiec, Justyna (Tematy i Konteksty, 2016)
The aim of the article is to present and analyze two sixteenth-century, nontrinitarian publications (The Matters and Words of Jesus Christ and The Second Book of St Luke by Thomas Falconius) which were created in close connection with the Brest Bible in 1566. The first part contains general information about the physical attributes of the works, showing typographical associations with the Brest Bible. Then, I present the work’s editorial layout and binding, regarding them as a valuable source of knowledge about Brest as a publishing centre in the sixteenth century. The final part contains an analysis of the most important doctrinal (nontrinitarian) theses posed by Thomas Falconius.